2015
DOI: 10.5455/ijmsph.2015.2509201434
|View full text |Cite
|
Sign up to set email alerts
|

Biomedical waste management practices in a tertiary-care hospital in Punjab

Abstract: Background: Biomedical waste (BMW) has recently emerged as an issue of major concern not only to hospitals and nursing homes, but also to the environmental and law enforcing agencies, media, and the general public. BMW forms approximately 1%-2% of the total municipal solid waste stream.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
2
2
1
Order By: Relevance
“…6 Only 33.3% of class IV employees were vaccinated against Hepatitis B which is very low and was similar as reported by Kalia et al previously. 23 Injury reporting due to sharps was low among all groups in our study whereas in Mathur et al study approximately 60% of doctors reported injury due to sharps. 6 Stein et al reported that only 37% of study population ever reported needle stick injury.…”
Section: Discussioncontrasting
confidence: 67%
“…6 Only 33.3% of class IV employees were vaccinated against Hepatitis B which is very low and was similar as reported by Kalia et al previously. 23 Injury reporting due to sharps was low among all groups in our study whereas in Mathur et al study approximately 60% of doctors reported injury due to sharps. 6 Stein et al reported that only 37% of study population ever reported needle stick injury.…”
Section: Discussioncontrasting
confidence: 67%
“…Knowledge about diseases transmitted by BMW was good (94.4%) among majority of doctors, nurses and lab technicians and class IV employees in our study as show on table 5:1. This finding was compatible with previous studies except in class IV employees which show poor level of knowledge in that study [40][41][42][43][44][45][46][47][48][49]. This exception in our study may be due to high incidence of occurrence in our community.…”
Section: Discussionsupporting
confidence: 92%
“…Malini et al similarly established that majority of qualified he Maximum number of health staff followed proper disposal of BMW in specific containers similar to a previous study [40]. Only (51.7%) of nurses and (58.8%) of class IV employees were vaccinated against diseases transmitted by BMW which is reasonable and was similar as reported by Kalia et al previously majority of qualified health professionals followed appropriate BMW management practices during observation noted that there is some defect in the practice of health worker in spite of good level of practices [52]. Percentage of knowledge of the participates regarding BMW = 73.5% Percentage of practice of the participates regarding BMW = 81.4%…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…7 Kalia et al in their study showed that immunization status for tetanus and hepatitis B is satisfactory among nurses and laboratory technicians. 8 In this study the waste segregation practices were more satisfactory among doctors and nurses than laboratory technicians. The practice of waste segregation was maximum among the staff nurses (71.8%) followed by doctors (61.7%) and laboratory technicians (27.8%).…”
Section: Discussionmentioning
confidence: 59%